BAYANI, BURHANI, AND IRFANI REASONING IN ISLAMIC STUDIES - Ernawati, Tuti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2023)
This paper aims to understand the reasoning of Bayani, Burhani, and Irfani through a descriptive qualitative approach, namely by collecting various kinds of literature related to Bayani, Burhani, and Irfani. Bayani is a methodology of thinking based on texts, this method existed before Islam came, Irfani is a method of thinking based on approaches and direct experience related to religious spiritual reality. The method used in this research is literature study, which tries to reveal by analyzing textually and contextually. Textual analysis is carried out using several interpretations and relevant journals, while contextual analysis is the author's understanding so as to form a complete understanding. The results of the discussion can be described as follows: Bayani is a thinking methodology based on the texts, this method existed before Islam came. It is the sacred text that has full authority in giving the direction and meaning of the truth, while the ratio only functions as a guard for the security of the text’s authority. Irfani is a method of thinking that is based on a direct approach and experience related to religious spiritual reality. And Burhani is a thinking methodology that is not based on texts or experience but on the basis of logical truths that when the existence of sacred texts and spiritual experiences can only be accepted if they are in accordance with logical rules